2006
DOI: 10.1158/0008-5472.can-06-0503
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of BRCA1 and BRCA2 Mutations in a Population-Based Study of Breast Cancer in White and Black American Women Ages 35 to 64 Years

Abstract: Although well studied in families at high-risk, the roles of mutations in the BRCA1 and BRCA2 genes are poorly understood in breast cancers in the general population, particularly in Black women and in age groups outside of the very young. We examined the prevalence and predictors of BRCA1 and BRCA2 mutations in 1,628 women with breast cancer and 674 women without breast cancer who participated in a multicenter population-based case-control study of Black and White women, 35 to 64 years of age. Among cases, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
238
2
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 332 publications
(271 citation statements)
references
References 50 publications
17
238
2
9
Order By: Relevance
“…As the proteintruncating BRCA2 mutations were detected in Caucasians only, the prevalence of such mutations in whites is 0.78% (95%CI 0.09 -2.81%). Recently, Malone et al (2006) reported a weighted prevalence of protein-truncating BRCA2 mutations of 0.1% (95%CI 0.0 -0.3%) among US population-based Caucasian control women aged 35 -64 years. Assuming that the prevalence of disease-associated BRCA2 mutations among Caucasian men in the general population is similar to the prevalence of such mutations reported for US Caucasian women, the estimated RR of prostate cancer in white men o55 years of age associated with carrying a protein-truncating BRCA2 mutation is 7.78 (95%CI 1.80 -9.37).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the proteintruncating BRCA2 mutations were detected in Caucasians only, the prevalence of such mutations in whites is 0.78% (95%CI 0.09 -2.81%). Recently, Malone et al (2006) reported a weighted prevalence of protein-truncating BRCA2 mutations of 0.1% (95%CI 0.0 -0.3%) among US population-based Caucasian control women aged 35 -64 years. Assuming that the prevalence of disease-associated BRCA2 mutations among Caucasian men in the general population is similar to the prevalence of such mutations reported for US Caucasian women, the estimated RR of prostate cancer in white men o55 years of age associated with carrying a protein-truncating BRCA2 mutation is 7.78 (95%CI 1.80 -9.37).…”
Section: Resultsmentioning
confidence: 99%
“…As both disease-associated BRCA2 mutation carriers were Caucasian, the prevalence of such mutations in whites is 0.78% (95%CI 0.09 -2.81%); the estimated RR of prostate cancer is 7.8 (95%CI 1.8 -9.4) in Caucasian BRCA2 mutation carriers. Although this represents a substantially elevated RR of earlier-onset prostate cancer associated with carrying a germline protein-truncating BRCA2 mutation, such mutations are very rare (B0.1%) in the general US population (Malone et al, 2006). The estimated cumulative risk (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations